System Identification Modeling Of Arm Rehabilitation Devices - Jali, Mohd Hafiz; Ahmad Izzuddin, Tarmizi; Ghazali, Rozaimi; Mustafa, Na Eisyah Sarah; Jaafar, Hazriq Izzuan; Sarkawi, Hafez (Little Lion Scientific Islamabad Pakistan, 2015)
-